Epistemic injustice and mental health research: A pragmatic approach to working with lived experience expertise - Okoroji, Celestin; Mackay, Tanya; Robotham, Dan; Beckford, Davino; Pinfold, Vanessa (Frontiers in Psychiatry, 2023)
‘Epistemic injustice’ refers to how people from marginalised groups are denied opportunities to create knowledge and derive meaning from their experiences. In the mental health field, epistemic injustice occurs in both research and service delivery systems and particularly impacts people from racialised communities. Lived experience involvement and leadership are often proposed as methods of combatting epistemic injustice, a tool for ensuring the views of people at the centre of an issue are heard and inform decision-making. However, this approach is not without challenges. In this paper, we draw on our work as intermediary organisations that centre lived experience perspectives to challenge epistemic injustice. We highlight two problems we have identified in working in the mental health research field: ‘elite capture’ and ‘epistemic exploitation’. We believe that these problems are barriers to the radical and structural change required for epistemic justice to occur. We propose a pragmatic approach to addressing these issues. Based on our work we suggest three considerations for researchers and our own organisations to consider when involving people with lived experience. These include reflecting on the purpose of creating knowledge, with a focus on impact. Embedding lived experience roles, with appropriate employment, support and remuneration, and acknowledging that it may be necessary to work alongside existing systems as a ‘critical friend’ whilst developing new spaces and structures for alternative forms of knowledge. Finally, the mental health research system needs to change. We believe these three considerations will help us better move towards epistemic justice in mental health research.